Alternative Methodology for Occupational Dose Estimation in Cardiac Electrophysiology Procedures (Brazilian Journal of Radiation Sciences, 2022)
Fluoroscopy-guided cardiac electrophysiology procedures are among the most critical x-ray exposures. However, occupational doses are still little-known. In this study, an alternative methodology was developed to estimate the occupational dose and evaluated its optimization in cardiac electro-physiology procedures. The procedures were reproduced by simulation and the dose rates of the staff were measured at chest and eyes height through electronic dosimeters. The dose rate for different modes of operation and FOV were evaluated. The occupational dose was estimated through the product of the dose rate in the staff's position in the room, the median time of exposure and the mean of these procedures performed by the HCPA in 2019. As a result, it was observed that the decreasing order of the estimated occupational dose was Physician A - Physician R - Nursing Staff and Radiographer - Physician B and Supplier, with the following values in mSv/year of 6.16 - 3.98 - 2.54 - 2.17, respectively. A 37.04% reduction in the occupational dose was observed with the change in FOV, up to 59.26% with different modes of acquisition and 31.82% distancing 50 cm from the most exposed position. The dose of staff is significant. However, due to the optimization of protocols already implemented in HCPA, the estimated doses are in accordance with the recommended dose limits. As optimization actions verified in this study, it is suggested the proper selection of FOV, the adoption of acquisition modes with dose reduction and the distance from the x-ray source.